Predicting hepatitis B e Antigen seroconversion after pregnancy—The SydPregScore. (8th August 2022) - Thilakanathan, Cynthuja; Kayes, Tahrima; Di Girolamo, Julia; Nguyen, Vi; Glass, Anne; Manandhar, Sicha; Lawler, Joseph; Meredith, Chris; Maley, Michael; Lloyd, Andrew; Levy, Miriam T.
Abstract: Background and Aims: Achieving Hepatitis B e antigen seroconversion (HBeAg SC) at an earlier age confers a better prognosis. We examined baseline and post‐partum factors associated with HBeAg SC after pregnancy. We developed a tool, the SydPregScore, to estimate the likelihood of HBeAg SC in the years after pregnancy. Methods: A retrospective analysis of an HBeAg‐positive pregnant cohort was conducted. Variables including baseline age, parity, alanine aminotransferase level, HBV viral load, quantitative HBsAg, use of antiviral therapy and post‐partum flare were collected. Univariate and multivariate Cox regression analyses to determine predictors of HBeAg SC and develop a predictor score were performed. Results: We analysed HBeAg SC rates in 220 pregnancies to 149 HBeAg‐positive women from 2006 to 2019. At baseline, their median age was 33 (IQR 29–37), ALT 23 U/L (IQR 17–33) and viral load 8 log10 IU/mL (IQR 6.3–8.2 log10 IU/mL). The majority (133/198, 67.2%) received short‐course antiviral therapy to prevent mother‐to‐child transmission, and 109/192 (56.8%) had a post‐partum flare. HBeAg SC occurred in 74/220 (33.6%) after pregnancy (median follow‐up 814 days, IQR 405–1531). Multivariate analysis identified baseline viral load <8 log10 IU/mL (HR 2.426 [1.224–4.809], p = .011), baseline ALT ≥2 ULN (HR 2.726 [1.299–5.721], p = .008) and age <35 (HR 2.859 [1.255–6.513], p = .012) to be positive predictors of HBeAg SC. The 'SydPreg Score' estimated the probability of HBeAg SC at 2000 days as 10%, 30%, 70% and 80% for 0, 1, 2, and 3 predictors respectively. Conclusion: The SydPreg Score allows the prediction of HBeAg SC in the years after pregnancy. Even in those without elevated ALT, age <35 and viral load <8 log10 IU/mL can identify women with a good chance of subsequent HBeAg SC. Those without a chance may benefit from viral suppression.